Controlling hydrogen evolution reaction activity on Ni core–Pt island nanoparticles by tuning the size of the Pt islands. Issue 22 (18th February 2021) - Alinezhad, Ali; Benedetti, Tania M.; Lian, Jiaxin; Gonçales, Vinicius R.; Gooding, J. Justin; Tilley, Richard D.
Abstract : Pt islands with different sizes were grown on amorphous Ni nanoparticles, allowing the tuning of the Pt–Ni interface without changing the hydrogen binding energy of the Pt sites. Abstract : Pt islands with different sizes were grown on amorphous Ni nanoparticles, allowing the tuning of the Pt–Ni interface without changing the hydrogen binding energy of the Pt sites. As a result, the HER activity of the electrocatalysts increases by decreasing the size of the Pt islands due to the greater surface area of the Pt–Ni interfaces.